PENGARUH KEPEMILIKAN INSTITUSIONAL TERHADAP BIAYA KEAGENAN PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA (Periode 2015-2019) - Dewi, Pitra Puspa; Makhdalena, Makhdalena; Gimin, Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to examine the effect of institutional ownership on agency costs in manufacturing companies in the basic and chemical industrial sectors listed on the Indonesia Stock Exchange (2015-2019 period). The population of this study is all manufacturing companies that have data on institutional ownership and agency costs listed on the Indonesia Stock Exchange. The Companies are limited by using specific criteria or types that can provide the required information, which is 9 companies. This study uses secondary data derived from the financial statements of each company as well as from other sources such as supporting records in the company and supporting websites through www.idx.co.id or the website of each company regarding reports company finances. The analytical technique used in this research is simple linear regression with the help of the statistical software package for social science (SPSS). The results of this study indicate that if using a significant value of 5%, institutional ownership has no significant effect on agency costs. this is evidanced by the result of the t test which shows that t_count is 1.206 and t_table is 2.01669. the higher the institutional ownership, the lower the agency costs.Key Word: Institutional Ownership, Agency Cost.